(untitled) (Academia Science Repository, 2023)
Preeclampsia (PE) occupies a leading position in the structure of pathology during pregnancy, due to the lack of early and reliable diagnostic criteria, effective prevention and treatment measures. Preeclampsia is a systemic, multi-organ endotheliopathy that affects the kidneys, heart, liver, and brain.Preeclampsia (PE) is a serious medical and social problem throughout the world, as it remains one of the main causes of perinatal and maternal mortality.